BCM543: Building Services Engineering II / College of Built Environment - UiTM, College of Built Environment (2017)
To create an understanding of the design and installation of the services commonly provided in habitable buildings. The learning process includes a study on specific characteristics of each type of service, the safety requirements for both installation and operation and the relationship between services systems and the building envelope.